2015
DOI: 10.1249/mss.0000000000000595
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Training Intensity on Nonalcoholic Fatty Liver Disease

Abstract: The current findings suggest that VIT is an alternative way of exercise training to combat hepatic steatosis associated with an obese and impaired glucose tolerance phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 49 publications
1
45
2
3
Order By: Relevance
“…In a recent study, we also found that EX, performed at either moderate or vigorous intensity, alleviated obesity, whole body insulin resistance and hepatic steatosis in HFD-induced mice. 24 Linden et al 29 found that the combination of CR and metformin resulted in greater reductions in adiposity and hepatic de novo lipogenesis than did metformin alone. Using a HFD-induced mouse model, Huang et al 30 showed that CR or EX resulted in significant attenuations of metabolic abnormalities, with greater attenuations of obesity and insulin resistance observed with the combination of CR and EX than with CR or EX alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, we also found that EX, performed at either moderate or vigorous intensity, alleviated obesity, whole body insulin resistance and hepatic steatosis in HFD-induced mice. 24 Linden et al 29 found that the combination of CR and metformin resulted in greater reductions in adiposity and hepatic de novo lipogenesis than did metformin alone. Using a HFD-induced mouse model, Huang et al 30 showed that CR or EX resulted in significant attenuations of metabolic abnormalities, with greater attenuations of obesity and insulin resistance observed with the combination of CR and EX than with CR or EX alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have suggested that the adiponectin receptor-mediated signaling pathway may play an important role in mediating the additive benefits of the combination of EX and CR in the treatment of NAFLD. [21][22][23][24] Adiponectin, which is abundantly present in circulating plasma, is an adipocyte-derived protein involved in energy homeostasis by promoting glucose uptake into skeletal muscle and liver and stimulating fatty acid oxidation in tissues. Adiponectin exerts its actions via both muscle-specific adiponectin receptor 1 (AdipoR1) and liverspecific adiponectin receptor 2 (AdipoR2).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, under conditions that are associated with an increase of intrahepatic lipid content such as NASH, vigorous activity that allows reducing the overall hepatic lipid content was shown to be more favorable than moderate activity. This was exemplarily demonstrated in a high-fat diet-induced obese mouse model, in which vigorous-intensity and interval treadmill running was more effective in alleviating hepatic steatosis than moderate-intensity and continuous treadmill running (Cho et al, 2015). These results were also confirmed in patients with NAFLD determined by liver biopsy: While vigorous-intensity exercise inversely correlated with NAFLD severity, there was no such effect visible regarding either moderate-intensity training or the total amount of exercise (Kistler et al, 2011).…”
Section: Significance Of Exercise For the Therapy Of Cldmentioning
confidence: 96%
“…Cross-sectional data suggest that vigorous exercise intensity per se is required for histological improvement in the liver [23]; however, this is based on self-report data. Recent research from obese rodent models also suggests a superior benefit of high-intensity training compared with moderate-intensity continuous exercise on liver fat and markers of liver injury typically associated with NASH [24]. However, until further evidence is available from human clinical trials, exercise for patients with NASH should be prescribed at similar exercise levels, cognizant of co-morbidities and in conjunction with lifestyle changes and pharmacotherapy [9].…”
Section: Exercise For Patients With Nashmentioning
confidence: 99%